The relationship between health literacy and problematic internet use in Chinese college students: The mediating effect of subject well-being and moderating effect of social support - Liu, Gongli; Qi, Fei; Gao, Qian; Huo, Lingling; Jia, Xiaorong; Wang, Rui; Wu, Yibo; Li, Shanpeng (Journal of affective disorders, 2024)
The issue of problematic Internet use (PIU) amongst college students is emerging as a major concern for mental health. Factors such as health literacy, subjective well-being and the extent of social support may be critical in preventing PIU. However, the complex relationship between these factors has not been extensively explored in research. A national cross-sectional study based on multistage random sampling was conducted in China in 2022. The subjects for this study were 7669 college students who completed a set of questionnaires assessing their health literacy, subjective well-being, PIU and social support. A structural equation model (SEM) was utilised for exploring the mediating effect of subjective well-being, and the PROCESS macro was used to test the moderating effect of social support. After controlling for demographic factors, a significantly negative correlation was found between health literacy and PIU, and subjective well-being partially mediated this relationship. In addition, social support was negatively related to PIU and could moderate the relationship between health literacy and subjective well-being and between subjective well-being and PIU. This is a cross-sectional study, and the results cannot inform the causality between these variables. Results revealed that the relationship between health literacy and PIU was partially mediated by subjective well-being in college students. The correlation between health literacy and subjective well-being and between subjective well-being and PIU were moderated by social support. Thus, future interventions for college students' PIU should be facilitated by improving health literacy, subjective well-being and social support. •This article used the data from a cross-sectional investigation in mainland China in 2022 to describe the current situation of problematic Internet use amongst Chinese college students.•In this study, we explored the relationship between health literacy and problematic Internet use. And based on stress-coping theory, we assess the mediating role of the subjective well-being in the relationship between health literacy and problematic Internet use.•Then based on protective factor-protective factor model, we assess the moderating effect of social support and explained the relationship between health literacy, subjective well-being, problematic Internet use, and social support.